Smart city – the concept of future - Ch. Srinivasa Rao, Dr. NSSR Murthy, (International Journal of Scientific Research and Management (IJSRM), 2015)
Success of a country depends on Urbanisation and development of economy. It was prdicted that by 2050, urban population rises to 76% from existing 50%. The level of comfort and quality of life depends on sustainability of economic development, mobility, environment, governance. Smart cities are solution for all these problems which carry out all features. The paper discusses the various layers of smart city , its aspects and government roll in developing smart cities.